SMART CLASSROOM ENVIRONMENTAL PARAMETERS AS A PARAMETER OF ADAPTIVE LEARNING - Radosavljevic, Vitomir; Radosavljevic, Slavica; Jelic, Gordana (PEOPLE: International Journal of Social Sciences, 2019)
This paper presents results of the research aimed at establishing the possibility of using a physical environmental parameter (λ) as one of the parameters of adaptive learning in smart classrooms. In this research, the parameter quantifying physical environmental parameters of a smart classroom into a single value was introduced and the relevance of the usage of the introduced parameter as a criterion of adaptive learning in a smart classroom was evaluated. The presentation of multiple environmental parameters through one unique parameter facilitated the realization of adaptation process, especially in the case of applying several adaptation criteria. An overall of 64 third-year students of the ICT College in Belgrade participated in the research. The implemented research drew certain conclusions. The relevance of using the parameter (λ) as the criterion of adaptive learning in smart classrooms was confirmed.